2002
DOI: 10.1002/j.2048-7940.2002.tb01996.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Trajectory of Unpartnered Elders After Myocardial Infarction: An Analysis of Daily Diaries

Abstract: The study reported here analyzed daily diary entries of unpartnered elders after myocardial infarction (MI) to gain perspective into their recovery. A total of 33 diaries were included as part of the qualitative analysis of the larger study referred to above. Diary content was evaluated through qualitative descriptive analysis. Six categories--activities of daily living, exercise practices, social support, symptom reporting, healthcare activities, and health-related expenses--were identified from the diaries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Roebuck et al (5) also stated that women suffering from an MI expressed isolation and loneliness. In the present study, the women reported that a source of stress was their concern that other conditions and diseases would trigger an MI , which is in line with Rankin et al (24), who highlight multiple chronic illnesses as a significant stress factor. For example, in the present study the women with diabetes were aware that they were at a risk of suffering an MI, and thoughts about the association between diabetes and CHD resulted in stress.…”
supporting
confidence: 90%
“…Roebuck et al (5) also stated that women suffering from an MI expressed isolation and loneliness. In the present study, the women reported that a source of stress was their concern that other conditions and diseases would trigger an MI , which is in line with Rankin et al (24), who highlight multiple chronic illnesses as a significant stress factor. For example, in the present study the women with diabetes were aware that they were at a risk of suffering an MI, and thoughts about the association between diabetes and CHD resulted in stress.…”
supporting
confidence: 90%
“…75,77,79 Other symptoms reported during the first few weeks to months after hospitalization among both ACS and cardiac surgical patients included sleep disturbances, gastrointestinal distress, dizziness, palpitations, appetite problems (eg, loss of appetite), and swelling in the legs and feet. 32,62,63,65,73 Psychosocial and Cognitive Impairment Symptoms Experienced…”
Section: Physical Symptoms Experiencedmentioning
confidence: 99%
“…There is also an aspect regarding the effectiveness of the measures implemented [46][47][48][49][50][51][52] and the different treatments [53][54][55]. Another investigated aspect concerns lifestyle, with regard to dietary habits, healthy lifestyle [56], comorbidities [43,57] (smoking and/or alcohol), but also environmental factors like atmospheric pollution.…”
Section: Discussionmentioning
confidence: 99%